PENGEMBANGAN MEDIA POP-UP BOOK DIGITAL BARTER FABEL UNTUK MENUNJANG LITERASI MEMBACA SISWA KELAS IV SD - Salsabila, Annisa; Dian Purnama Putri, Ragil (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low reading literacy of students resulting from the suboptimal use of digital media in instruction. Consequently, the "Barter Fabel" Digital Pop-Up Book was developed, integrating audio and visual elements to support reading literacy. The study aimed to determine the development steps, product feasibility based on expert assessments, and the responses of teachers and students to the media's use. A Research and Development (R&D) method employing the ADDIE model was utilized. The research subjects were fourth-grade students at SD N Sriharjo. Data collection involved interviews, observations, and assessment sheets, with data analyzed using both descriptive qualitative and quantitative methods. The results indicate that the "Barter Fabel" Digital Pop-Up Book was successfully developed through the five ADDIE stages: analysis, design, development, implementation, and evaluation. Media expert assessment yielded a score of 96% (classified as "Highly Feasible"), while content expert assessment scored 80% ("Feasible"). Language expert assessment scored 72% ("Feasible"), and instructional expert assessment scored 96% ("Highly Feasible"). Overall, the expert assessment of product quality resulted in an average score of 86% ("Highly Feasible"). Teacher response scored 100% ("Very Good"), with comments noting the media's high quality and engaging nature, as well as the alignment of its content with learning objectives. Student response scored 95.7% ("Very Good"), with comments highlighting that the engaging media fostered enthusiasm for reading and understanding stories during narrative text lessons. The study's implications suggest that the "Barter Fabel" Digital Pop-Up Book is suitable for supporting reading literacy among fourth-grade elementary students.